Growth of Sheep of Chokla Breed Under Different Systems of Grazing on Rangelands In The Arid Zone of Western Rajasthan - Ahuja, L D; Vishwanatham, M K; Vyas, K K; Lal, Kundan (Annals of Arid Zone, 2016)
In order to evaluate the performance of sheep under different systems of grazing on rangelands in the arid zone of Rajasthan the growth rate of yearling ramlambs of the Chokla breed was studied on a 'Poor' condition rangeland with 310 mm rainfall (70 per cent during July, August & September 1966) from July 1966 to June 1967. The results revealed that :- 1. Different pastoral treatments did not significantly affect the growth rate of ramlambs. 2. Growth on yearlong basis was 19.3 kg per animal per year (range 17.8 to 20.S). 3~ Body growth was significantly affected by the seasons indirectly' through shifts in the nutritive value of different species o.n the range, Growth was highest (7.8 kg/animal) during July-August when forage is succulent and highly nutritive and least during October-November and March-April.